Myasthenic crisis and late deep vein thrombosis following thymectomy in a patient with myasthenia gravis: A case report. Issue 15 (April 2020) - Lin, Cheng-Yuan; Liu, Wei-Cheng; Chiang, Min-Hsien; Tsai, I-Ting; Chen, Jen-Yin; Cheng, Wan-Jung; Ho, Chun-Ning; Liao, Shu-Wei; Chu, Chin-Chen; Sun, Cheuk-Kwan; Hung, Kuo-Chuan
Abstract: Introduction: Surgical stress and pain are potential provoking factors for postoperative myasthenic crisis (POMC). We report the occurrence of early POMC and late deep vein thrombosis (DVT) in a man with myasthenia gravis (MG) undergoing thymectomy, addressing possible link between reversal of opioid overdose with naloxone and the triggering of POMC. Patient concerns: A 71-year-old man with impaired renal function (ie, estimated glomerular filtration rate [egfr]: 49.1 mL/min/1.73 m 2 ) with diagnosis of MG made 2 months ago was scheduled for thymectomy. After uncomplicated surgery, he experienced opioid overdose that was treated with naloxone. Hyperlactatemia then developed with a concomitant episode of hypertension. Three hours after reversal, he suffered from myasthenic crisis presenting with respiratory failure and difficult weaning from mechanical ventilation. Diagnosis: Stress-induced hyperlactatemia and subsequent myasthenic crisis Interventions: Pyridostigmine and immunosuppressive therapy with prednisolone were initiated. Hyperlactatemia subsided on postoperative day (POD) 5. Tracheal extubation was performed successfully on POD 6. Outcomes: During the course of hospitalization, his eGFR (ie, 88.9 mL/min/1.73 m 2 ) was found to improve postoperatively. After discharge from hospital, he developed DVT in the left femoral and popliteal veins on POD 24 when he was readmitted for immediate treatment with low-molecular-weight heparin. He was discharged without sequelae on POD 31. There was no recurrence of myasthenic crisis or DVT at 3-month follow-up. Conclusions: Following naloxone administration, hyperlactatemia may be an indicator of pain-related stress response, which is a potential provoking factor for myasthenic crisis. Additionally, patients with MG may have an increased risk of DVT possibly attributable to immune-mediated inflammation. These findings highlight the importance of perioperative avoidance of provoking factors including monitoring of stress-induced elevations in serum lactate concentration, close postoperative surveying for myasthenic crisis, and early recognition of possible thromboembolic complications in this patient population.